Report from the 2013 Hungarian Landscape Contractor’s Competition - Balogh, Péter István (4D Journal of Landscape Architecture and Garden Art, 2013)
The Hungarian Landscape Contractors’ Association (MAKEOSZ) organized its annual landscape contractors’ competition between April 10-14th 2013., again on the fairgrounds of Budapest - relating to the events of the construction exhibition Construma. The procedure of the contest was the same as at the earlier competitions: Each of the participating teams had a stand (of 25 or 50 square meters) at their disposal to create their own installation following a freely chosen subject.